2017
DOI: 10.1371/journal.pone.0190168
|View full text |Cite
|
Sign up to set email alerts
|

HSP90C interacts with PsbO1 and facilitates its thylakoid distribution from chloroplast stroma in Arabidopsis

Abstract: Arabidopsis plastidic HSP90C is an HSP90 family molecular chaperone that is required for chloroplast development and function. To understand the mechanism of action of HSP90C within the chloroplast, we conducted a yeast two-hybrid screening and revealed it interacts directly with the photosystem II extrinsic protein PsbO1, which performs a canonical function in the thylakoid lumen. To understand the biological significance of HSP90C-PsbO1 interaction, we investigated the role of HSP90C in modulating the stroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 76 publications
2
24
0
Order By: Relevance
“…After stratification in the dark at 4 °C for 3–4 d, seeds were cultured within a plant growth incubator set at 120 μmol m −2 s −1 , 16/8 h light/dark cycle at 22 °C. Transgenic seedlings used were generated previously ( Oh et al , 2014 ; Jiang et al , 2017 ). The T7-tagged SecY1 (SCY1) line was previously described ( Skalitzky et al , 2011 ) and was kindly provided by Dr Donna Fernandez (University of Wisconsin, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After stratification in the dark at 4 °C for 3–4 d, seeds were cultured within a plant growth incubator set at 120 μmol m −2 s −1 , 16/8 h light/dark cycle at 22 °C. Transgenic seedlings used were generated previously ( Oh et al , 2014 ; Jiang et al , 2017 ). The T7-tagged SecY1 (SCY1) line was previously described ( Skalitzky et al , 2011 ) and was kindly provided by Dr Donna Fernandez (University of Wisconsin, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, DnaK (Hsp70), DnaJ (Hsp40), and GroEL/ES (Hsp60/Hsp10) have been directly implicated in the Sec pathway through interaction with SecB ( Phillips and Silhavy, 1990 ; Sakr et al , 2010 ; Calloni et al , 2012 ; Castanie-Cornet et al ., 2014 ). In the plant Arabidopsis, we recently identified a transient interaction between HSP90C and PsbO1, a nuclear-encoded thylakoid lumen subunit of the PSII complex ( Jiang et al , 2017 ). We showed that inhibiting HSP90C activity altered the distribution of the PsbO1–green fluorescent protein (GFP) fusion protein between the stroma and thylakoid compartments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several plastidial proteins have been shown to localize as punctae or patches (Lee et al, 2001 ; Xu et al, 2005 ; Awai et al, 2006 ; Haswell and Meyerowitz, 2006 ; Seo et al, 2009 ; Tan et al, 2011 ; Liang et al, 2017 ; Li et al, 2017 ; Wang et al, 2017 ). While many of the reports have relied on transient protein over-expression in heterologous systems for their observations, stable transgenic lines that maintain a rather specific localization pattern for the fusion proteins, such as the poles of chloroplasts (Aranda-Sicilia et al, 2016 ), or clusters in the stroma (Jiang et al, 2017 ), have also been reported. We considered the possibility that stable transgenic lines that exhibit discrete fluorescent protein patches on the chloroplast envelope can serve as useful fiducial markers for assessing protein localization to different regions, including the extensions, of a chloroplast.…”
Section: Introductionmentioning
confidence: 99%
“…69 Arabidopsis plastidic heat shock protein 90 (Hsp90C) reportedly regulates the import of PsbO1 protein from the cytoplasm to thylakoid lumen. 72 How nitration of 9 Tyr of PsbO1 affects this regulation is not known. In addition, the fate of nitrated PsbO1 protein is an intriguing and important issue.…”
Section: Reappraisal Of Oxygen Evolution Analysismentioning
confidence: 99%